ATTEMPTED SYNTHESIS OF QUINONEMETHINE DERIVATIVE OF NOCARDICIN A ANALOGUES (Journal of Sciences, Islamic Republic of Iran)
The synthesis of some 13-lactams is described. 'The electronic activation of monocyclic B-lactams provided by a quinonemethine function was found to instabilize the 13-lactam ring toward nucleophilic: attack by water